АГРОӨНЕРКƏСІПТІК КЕШЕННІҢ ИННОВАЦИЯЛЫҚ ДАМУЫНЫҢ ƏДІСТЕМЕЛІК НЕГІЗІ (Journal of Economic Research & Business Administration, 2015)
The article is about the approach to the economic maintenance of the term "innovation". Classification of innovations, specificity, structure of the economic mechanism of innovative activity, a condition and factors ofinnovative development of agriculture, features of management of innovation processes in agriculture and priority directions of development of innovative potential are considered in the paper.